COMPLICAÇÃO NEUROLÓGICA DE AFECÇÃO OTORRINOLARINGOLÓGICA EM PEDIATRIA: UM RELATO DE CASO - Annah Rachel Graciano; Pedro Augusto Silva Ruas; Nayanne Pires Guimarães Gouveia de Souza; Rafael de Souza Bueno; Karla Cristina Naves de Carvalho (UniEVANGÉLICA, 2015)
Objective: To report a case of a pediatric patient with acute otitis media and sinusitis who evolved with intracranial complications. Case description: Male child, 4 years old, was admitted with persistent purulent otorrhea, mental confusion, irritability signals. The patient developed fever, convulsive seizures and motor impairment. The CT scan has accused hypodense subdural collection, front and unilateral. Antibiotic therapy was started and The patient was transferred for neurological and neurosurgical consultation for subsequently drainage of empyema. Comments: Otitis media and sinusitis correspond to the majority pediatric consultations, being the most common reason for drug prescription of antibiotics for children. The suppurative complications are rarely seen in developed countries, but occur frequently in children who have limited medical assistance. Although these diseases are often autolimited, there are complications with difficult management and high mortality rate.